Procurement of Trash Bins and Drainage Maintenance in Anjatan Baru Village, Indramayu Regency - Muhammad Fityan; Nur Subkhi; Mochammad Taufan (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
The work of each head of family in the Anjatan Baru Village community includes farming, entrepreneurship, livestock farming, civil servants, and others. Activities between residents and early childhood are quite good. Because of the large number of residents, the amount of household waste produced is also increasing. However, this is due to the lack of awareness of residents to dispose of waste in its place and manage the waste properly. Most residents still litter, especially in the drainage area which should be a water drainage channel, and residents still bury waste in the ground or burn it which may have a negative effect on the surrounding life. This problem causes clogged drainage channels, which has the potential to cause flooding, especially during the rainy season. Therefore, this program aims to increase public awareness of the importance of environmental cleanliness and good drainage maintenance. Activities carried out in this program include counseling, environmental cleaning, and procurement of trash bins. Counseling aims to provide information to the public about the right way to manage waste and the importance of maintaining environmental cleanliness. In addition, environmental cleaning is carried out to reduce the amount of scattered waste and improve the condition of existing drainage. The provision of trash bins is expected to make it easier for the community to dispose of trash in its place, thereby reducing the possibility of blockages in the drainage channels. The approach used in this supporting program is a qualitative approach in the form of surveys and observations. This is done to directly find out the condition of the cleanliness of the drainage channels and the environment around Anjatan Baru Village and to find out the drainage channel maintenance activities carried out by residents. Based on the analysis of the situation in Anjatan Baru Village. So we propose one of the supporting programs for the Real Work Lecture (KKN) activity in the form of drainage maintenance and procurement of trash bins. In addition to inviting the community to work together to clean the surrounding environment and drainage channels, this activity also provides counseling to the community that sediment and garbage that clogs drainage channels can cause water flow to be blocked so that it can cause flooding. With this drainage maintenance program and procurement of trash bins, it is hoped that the community will realize the importance of good drainage conditions and clean environmental conditions so that flooding can be avoided. The target of this program is the community of Anjatan Baru Village, especially people whose drainage conditions are blocked by garbage. The output target to be achieved in addition to compiling activity reports is to increase public awareness of the importance of a clean environment and cleaner drainage conditions that are not clogged with garbage. After this activity is completed, an evaluation will be carried out regarding the obstacles encountered during the implementation of the activity and how residents responded to the activity. Because this activity is carried out once, the evaluation of the implementation of the activity can be used as a learning experience so that obstacles during the first stage of the activity can be minimized in the second activity. The level of success of this activity itself is based on the condition of the environment and drainage channels before and after the implementation of the activity.